Ending Poverty and Hunger by 2030 : An Agenda for the Global Food System - World Bank Group (Washington, DC, 2015)
To permanently end poverty and hunger by 2030, the world needs a food system that can feed every person, every day, everywhere; that can raise real incomes of the poorest people; that can provide safe food and adequate nutrition; and that can better steward the world's natural resources. Urgently, we need a food system that is more resilient and that shifts from being a major contributor to climate change to being part of the solution. All these aspects are closely interlinked, calling for a more comprehensive approach to delivering a healthier and more prosperous future.